ERROR ANALYSIS OF SPOKEN RECOUNT TEXT MADE BY THE EIGHTH GRADERS OF BILINGUAL CLASS AT SMP NEGERI 1 BABAT (RETAIN, 2014)
ERROR ANALYSIS OF SPOKEN RECOUNT TEXT MADE BY THE EIGHTH GRADERS OF BILINGUAL CLASS AT SMP NEGERI 1 BABAT Muhammad Anwar Habibi English Language Education, Language and Arts Faculty, Surabaya State University anwarhabibi@rocketmail.com Esti Kurniasih, S.Pd., M.Pd. English Language Education, Language and Arts Faculty, Surabaya State University Abstrak Kemampuan berbiara siswa merupakan kemampuan yang alami. Pada satu sisi, siswa mampu menggunakan ilmu kebahasaan mereka dengan berbciara. Pada sisi yang lain, celah dari ilmu kebahasaan yang rendah akan terlihat dari bahasa lisan mereka yang didefinisikan sebagai kesalahan siswa atau Error. Untuk itu, bahasa lisan siswa bisa dijadikan sebagi tolok ukur yang tepat dalam mengukur kemampuan berbahasa mereka. Analisa kesalahan berbahasa siswa adalah salah satu metode yang berarti untuk mengisi celah ilmu kebahasaan siswa. Selanjutnya melalui evaluasi kesalahan berbahasa yang suah mereka buat, mereka mampu meningkatkan kecakapan berbahasa mereka secara bertahap. Studi deskriptif kualitatif ini bertujuan untuk menganalisa dan menjelaskan sebab dari macam-macam error yang telah dibuat oleh subjek penelitian ini dalam teks lisan berbentuk recount. Peneliti menggunakan klasifikasi kesalahan yang diusulkan oleh Hendrickson (1983) dan sebab kesalahan dari James dalam Ellis (2005). Peneliti juga menggunakan teori analisa data kualitaif yang diusulkan oleh Ary et al (2010). Untuk memperoleh data, peneliti merekam dan menuliskan teks lisan siswa berbentuk recount. Dari keseluruhan teks lisan siswa berbentuk recount ditemukan banyak kesalahan yang pada umumnya terjadi pada morphology dan phonology. Peneliti juga menemukan kesalahan yang terjadi pada lexicon dan syntax namun jarang terjadi. Dari keseluruhan kesalahan dalam morphology kebanyakan terjadi pada tense markers dan plural markers. Misanalysis dalam tata bahasa dan kurangnya kesadaran siswa untuk menggunakan tata bahasa yang baik dan benar dalam bahasa lisan merupakan sebab utama dari kesalahan-kesalahan siswa dalam teks lisan berbentuk recount mereka. Kata Kunci: analisa kesalahan, ketrampilan berbicara, teks recount, kelas bilingual, siswa kelas 8. Abstract Students’ spoken language is natural. On one hand, through the spoken language the students are going to be able to implement any language knowledge that they have learned. On the other hand, spoken language also provides the students’ gaps concern with lack of language knowledge that is referred as an error. Therefore, the students’ spoken language could be viewed as an exact object to measure their language ability. Analyzing the errors in learner’s language is a significant method to fill the students’ gaps. Then they are capable of enhancing their language aptitude through errors evaluation. This descriptive qualitative study is chiefly aimed to analyze the types and causes of errors that were made by the subject of this study on their spoken recount text. In this errors analysis of the students’ spoken recount text, error classification by Hendrickson (1983) and causes of error by James in Ellis (2005) are implemented to analyze and describe the errors and their causes. The spoken language data bring the researcher into recording and transcribing the students’ spoken recount text before analysis takes place to gain the data of this error analysis study. Theory of qualitative data proposed by Ary (2010) is implemented in analyzing the data of this study. The researcher found very many errors from the entire spoken recount texts. The errors are mostly occurred in morphology, then phonology. Lexicon and syntax are rarely occurred in the students’ spoken recount text. Morphological errors mostly occur in tense and plural markers. Misanalysis of the structure rules and lack of consciousness of applying them in oral communication mostly caused those errors occurred. Key words: error analysis, speaking skill, recount text, bilingual class, eighth graders. INTRODUCTION The very heart of using foreign language is able to speak the foreign language (Luoma, 2004). English has been included into the Indonesian education curriculum and taught since Elementary School level and recently young learners are also introduced to English in early age such as in Preschool class. The spoken form has been regarded as the primary form of language (Vachek, 1973 in Hughes, 2002). In fact, oral or written language produced by learners (Ellis, 2005:4) has the same purpose that is as means of communication. In addition, the main point of producing a language is that the speakers or the writers can extend any information they want to share using the senses they have. Learning language and constructing learner strategies (Wenden et al, 1987) are executed by the children through the instruction of the teacher inside the classroom as the continuation of childhood developmental phase in constructing language. Language learners will be curious about the language they are learning (McKay, 2006), so they are willing to accept any feedback that will upgrade their language knowledge. Then they will get into the evaluation part of learning language and the students will be able to use words and phrases fluently without very much conscious thought (Harmer, 2007). It seems rather peculiar to evaluate the students’ oral language by showing the errors they have made rather than the right one (Ellis, 1997). Students’ oral language is produced by the students naturally as the language features they have learned. Showing the error then noticing the right one will help the students to revise the students’ misunderstanding about a certain language feature then their language learning could develop gradually over the time. Yet, to show the students’ errors should be extended by the teacher as wise as possible. Ellis (1997) defines the error as reflection of learner’s knowledge and it occurs because the learner does not know the correct one. Lack of language knowledge such as pronunciation, accents, words use, vocabulary, and structure can be addressed to the students because of their error occurred. Therefore, they will learn this language knowledge gradually over the time. It means that the students will get their errors at the early moment of learning a new knowledge of a language lesson. Referring to the new lesson of the students in formal language learning level, recount and descriptive text are the new genres text for the 8th graders as in the Basic Competence of Junior High School students in speaking skill of the Badan Standar Nasional Pendidikan (BSNP), 2006. Giving information and sharing an account of what happened is the definition of the recount as the typical genre of Derewianka, 1992 in McKay, 2006. Giving and sharing an account of what happened to each of the students would be a fair topic of this error analysis study. Because, they will tell what in their mind using the represent words, phrase, and sentence rather than describing something because, they are going to have opportunities to cheat their friends’ words and it will limit their language knowledge. The spoken recount will refer to one of the genre texts for the 8th graders of Junior High School but it will be extended in the form of oral language not in written form. Based on the Basic Competence of Junior High School students in speaking skill of the BSNP, 2006 recount text is one of the genre texts that should be learned by the 8th graders as a new lesson because it is oriented in the first semester and they do not learn this text at the previous grade. Therefore, the new thing for the students will turn up the error of producing oral language. Therefore, they will be able to evaluate and revise their errors by knowing the errors they have made which are going to be the main data of this spoken recount text analysis study. The students will learn such text in the next semester. Thus, it is important to strengthen their language feature of recount text as oral language foundation. Different skill was analyzed in this study than others that differentiate the following error analysis study. Related to error analysis study, Prastiwi (2013) conducted a written error analysis of the eight graders on the problems of students’ competence in writing recount text in terms of its content and organization. In addition, the result of this study is that the content and organization of recount composition written by the 8th graders was categorized into average level. Therefore, this error analysis study is different from others error analysis studies that are mostly conducted in analyzing written language of the students. This error analysis study is chiefly aimed to analyze the errors and their causes that are found in spoken recount text made by the 8th graders of bilingual class at SMP Negeri 1 Babat. The students or the error maker will obtain more luck from this error analysis study because they will know and realize the error they have made when they are learning a new material. Being shown the error they have made sometimes will be brought up next to their mind so that they will be aware of having the similar errors. They will be noticeable about the language features as well and it will possibly help the students to self-correct the errors they have made (Ellis, 1997). Teacher is another one who will obtain the luck from this study; the errors known will be the reflection of some aspects of the teacher that they could be attributed to. For example, the teaching method, practice frequency, pronunciation, production, etc. He or she will know the measurement of the speaking skill mastered by the students from the errors they have made. The teacher will know which material should be emphasized in language teaching activity to cover the errors of the students in speaking skill particularly in spoken recount and recount text. METHOD In this study, the researcher used descriptive qualitative research. The researcher tried to describe and explain the students’ spoken recount error objectively and naturally as it existed. The data which are described by the researcher were taken from the students’ spoken recount text made by the 8th graders of bilingual class at SMP Negeri 1 Babat. The data of this study are in the form of words. Therefore, the researcher applied qualitative method where qualitative data are in the form of words or picture rather than numbers and statistics (Ary, 2010). The steps underwent by the researcher are collecting the students’ spoken recount data then transcribing them into written words. After that, the researcher organized and analyzed the error made by the students. Finally, the researcher extended the error analysis study of the spoken recount in the form of words as the result of this study. In addition, there was no any treatment given to the subjects of this study. The subjects of this study are the 8th graders of bilingual class at SMP Negeri 1 Babat and the researcher chose the A cluster. The researcher chose the 8th graders because they are learning recount text particularly in the first semester and will be continued to the next semester so this grade is the appropriate one to be the subjects of this study. Therefore, the researcher would like to know the errors that usually occur in students’ speaking. Ellis (2005) stated that the primary data of oral analysis are the recording of talk. The transcripts of the recording are not the data, but rather a representation of the data. However, the transcript and the recordings should be used together during the analysis. Data of this study are the errors which are found in the students’ speaking performance and the motives of the students for doing those errors. In analyzing the students’ spoken recount text, the researcher used the theory of Hendrickson (1983). The data source of this error analysis study is the spoken recount text performance made by the bilingual class of the 8th graders at SMP Negeri 1 Babat and the representation of the primary data are the transcript of the spoken recount text recording. The research instruments in this study were used to gain the answer of the research questions. In this study, the researcher used two instruments. The primary instrument used in qualitative research is the researcher himself (Ary, 2010). In fact, the researcher conducted the research, collected data until analyzed the data of the study by himself. So the researcher is the primary instrument of this study that is used to answer the first and second research question. To support the primary instrument gained the data, the researcher used a recording as a tool of instrument because the form of the primary data is in the form of audio recording. Audio recording is now widely used to show the language use occur naturally (Ellis et al, 2005). There are three principle methods of collecting sample, they are: (1). Pencil and paper; (2). Audio recording; (3). Video recording (Ellis et al, 2005). In this study, the researcher used the audio recording because the data of this study are in the form of spoken data. Therefore, the first step done by the researcher was recording the spoken recount text made by the bilingual class of the 8th graders at SMP Negeri 1 Babat. After recording the students’ spoken recount text, the researcher transcribed the recording into written transcription to ease the researcher in analyzing the students’ spoken recount text to find the type of errors. The recording perhaps eases an analysis to go back to the oral performance repeatedly. It helps to ensure that the transcription is detailed and accurate (Ellis et al, 2005). The next step is analyzing the students’ spoken recount text through their transcription. The theory of Hendrickson (1983) was used to classify the students’ errors found in their spoken performance. By classifying the categories of errors, the researcher will be able to construct the open questionnaire that was used to know the motives of the students for doing those errors. Then the researcher described the data systematically to get the best understanding based on the research questions. There are some theories which define the stages of qualitative data analysis, for instance, Cresswell (2007), Marshall and Roshman (2006), Maxwell (2005), Wolcott (1994), and Ary (2010). Moreover, they have different stages that should be done by the qualitative researcher in analyzing data. In this study, the researcher applied the theory of qualitative data analysis by Ary et al (2010) that consists of familiarizing-organizing, coding-reducing, and interpreting-representing. Familiarizing and organizing is the first stage of analyzing data of this study. In this study, the researcher familiarized himself with the data (Ary, 2010). Listening repeatedly is one way to familiarize with the data because the data of this study are in the form of spoken data. To ease the researcher, he made the transcription of the recording. After being familiar with the data, the researcher organized the data so that the researcher is capable of analyzing the data through the next stage. The second stage is coding and reducing. Coding itself is not to sum but to break apart the data (Ary, 2010). In this stage, the researcher coded the students’ spoken recount transcriptions to separate the data based on the coding. In addition, this was used to ease the researcher in analyzing the error of each student’s spoken transcription. After being coded and analyzed in detail based on the theory used, the data were then coded in larger coding. The large code is the part where the students’ spoken transcription put into three codes based on the content and the errors found. Excellent, good, and poor are the codes used to divide the data into large group and each group will be represented by certain data to be presented in the finding and discussion part. In this stage, unfortunately the researcher did not reduce any data that had been collected because the researcher intentionally analyzed all the students’ spoken recount text transcription. The last stage is interpreting and representing. Ary (2010) stated that interpretation is about emerging the meaning, telling whatever it exists, providing an explanation and developing the reasonable explanations. To interpret the data, the researcher used the theory of error analysis as the set of rule so that the researcher is able to interpret them in detail. In addition, this interpretation will be understandable by the availability of the visual representation of the data. The researcher used the table to explain the errors found in detail and chart to show the percentage of the error frequencies or amount. RESULT AND DISCUSSION After recording the spoken recount text then the researcher transcribed them into words with normal orthography supported with codes that are used to represent the data representation as it is existed. In analyzing the data, the researcher implemented familiarizing-organizing and coding-reducing theory of qualitative data analysis by Ari et al (2010). In this chapter, the researcher implemented the interpreting-representing stage of this theory. The entire errors that are found by the researcher occurred in each error linguistic proposed by Hendrickson (1983). After classifying the errors, the researcher found that the local errors found mostly occurred in morphology, phonology, syntax, and lexicon. While the global errors found by the researcher mostly occurred in lexicon, syntax, and morphology. In addition, the researcher did not find any global errors that occurred in phonology. Type of errors Number of local errors Number of global errors Lexicon 55 5 Syntax 63 2 Morphology 150 1 Phonology 95 - Total 363 8 Interlingual errors are caused by the mother tongue interference in learning either second or foreign language. This interference probably gives not only positive but also negative effects that is commonly called transfer. Ellis (1997) stated that facilitation given by the first language in learning second language is positive transfer. While negative transfer is the first language role as the source of errors. In this study, the researcher found so many negative transfer cases where most of the entire students’ spoken recount texts were composed and spoken by applying the first language structure rather than the English structure. Interlingual errors in this study occurred in lexicon, syntax, morphology and phonology in particular as the speech of the language learner that contains the characteristic of transfer in its pronunciation and intonation pattern. The errors that were caused by interlingual are mostly occurred in morphology, phonology, syntax and lexicon. To be exact, the entire errors found in spoken recount text made by the subject of this study are assumed as interlingual errors. As Ellis (1997) stated that transfer is common in second language learners’ speech. The second major in explaining errors is intralingual. This major reflects the universal process of learning strategy applied by the learners (Ellis, 1997). The intralingual consists of false analogy, misanalysis, incomplete rule application, exploiting redundancy, overlooking co-occurrence restriction, and system-simplification (James, 1998 in Ellis, 1997). Each error made by the students may have more than one cause (Tarone, 2009). Therefore, the researcher found some errors that have more than one cause that will increase the number of cause of error than the errors itself. The researcher found fewer errors that are caused by the intralingual errors than others that are caused by interlingual. These because of the phonological errors are completely caused by interlingual. An error made by the students that is caused by the system-simplification is rarely occurred among the whole of errors. The cause of this error occurs is when the students simplified the rule of the system in English to communicate rather than use the complete one. In false analogy or a kind of overgeneralization error that are caused by the students’ false analogy is higher than system simplification. This false analogy mostly occurs in incorrect chosen words where the speaker or the subject thought it was correct. For example, the subject prefers to use long to show the distance rather than far. Literally, those words have different meaning, but the subject’s analogy call it same or similar. The subjects also overgeneralized forms that they have found to be easy to learn and process (Ellis, 1997). The use of ‘eated’ in the place of ‘ate’, for instance. The errors of overlooking co-occurrence are in same level as the false analogy errors. The errors caused by overlooking occur in inappropriate words chosen who have similar meaning with others but have different collocation. For example, one of the subjects used ‘fourteen p.m.’ in place of ‘two p.m.’. The researcher found higher errors that are caused by incomplete rule application than the previous ones. Incomplete rule application occurs in inappropriate rules applied by the students. They prefer to restructure the grammatical systems with their own as Ellis (1997) stated that restructuring grammatical rules is prevalent in second language acquisition. Word order errors are mostly caused by the incomplete rule application where the students mentioned the part of speech component of a sentence, but they arranged it in the wrong arrangement that trespassing the grammatical rules of English language in particular. From the entire errors caused by incomplete rule application are mostly occurred in word order. Errors that are caused by exploiting redundancy often occurred in students’ spoken recount text. James in Ellis (1997) stated that exploiting redundancy is leaving the grammatical features that do not contribute to the meaning of an utterance, for example, omitting –s in verbs of third person singular. The same case also occurs in plural markers and possessive adjectives errors where most of the students leave the –s in plural markers and –‘s in possessive adjective. Learners find difficulties of speaking in full sentences so they often leave the words. In second language acquisition, this case is called propositional simplification that happens in the early second language learner speech (Ellis, 1997). Most of errors found in students’ spoken recount text are caused by misanalysis. The errors that are caused by misanalysis mostly occurred in verbs and tense markers. The presence, absence, and inappropriateness of verbs are the consideration of the verb errors that are caused by misanalysis. While inappropriate form of verbs is the consideration of the tense marker errors, for example, the use of present participle verb in past tense verb. CONCLUSION AND SUGGESTIONS Conclusion The researcher found that the entire bilingual students made errors in their spoken recount text. From entire spoken recount texts made by each student of bilingual class, the errors are mostly occurred in morphology, phonology, syntax, and lexicon. The errors of lexicon are mostly occurred in verbs, noun, and adverb. And errors of adjective are rarely occurred. Therefore, from the whole errors of lexicon are mostly occurred in preposition, possessive adjective, articles, word order. Moreover, errors in syntactic class, modals, conjunction, and demonstrative adjective are rarely occurred. The errors of phonology occurred in mispronunciation entirely. Moreover, most of errors found by the researcher occurred in morphology and tense markers are dominants than plural and negative markers. The causes of the errors made by the students were concerned in the second research question of this study. The researcher found that errors made by the bilingual students are dominantly caused by the interlingual errors or the mother tongue interference. The researcher also found fewer errors that are caused by the intralingual errors than interlingual. System simplification rarely caused the production of errors found in intralingual. False analogy and overlooking co-occurrence caused errors production more than system simplification. In addition, the entire errors are mostly caused by misanalysis, exploiting redundancy, and incomplete rule application. Based on the result of this error analysis on the spoken recount text made by the bilingual students, the researcher concluded that the students’ speaking ability is weak. It is reflected from the number of errors found by the researcher. On one hand, the advanced number of errors that is caused by the interlingual errors is possible because English language in the students’ point of view is a foreign language that is implemented as the medium language in teaching and learning activity in bilingual class. Moreover, they should be aware of the interlingual errors so that they are not in fossilization (Ellis, 1997). In fact, the descending of students’ consciousness and awareness in implementing grammatical rules in spoken language to turn up the readers’ comprehension toward the content of the spoken recount text affected the errors production in their spoken language. Suggestions After conducting an error analysis on the students’ spoken recount text and resulting the finding as above, the researcher suggests not only the teacher but also the students. In fact, the students made very many errors in their spoken recount then the teacher should evaluate the errors found so that the students are able to learn from their errors. From the teacher’s evaluation, the students will be able to develop their language capability gradually, especially in speaking ability. The teacher should also emphasize the material where the errors occurred, it could be in the form of review or discussion. Moreover, the teacher should motivate the students to be aware of the grammar rules in speaking and to have self-consciousness in practicing English. Meanwhile, the researcher suggests the students to be able to learn the errors that they have made so that they could enhance their own language ability gradually. Then they also should raise their awareness and consciousness in implementing grammar rules in communication as well to turn up the readers’ comprehension, on behalf of bilingual class tittle that requires them so that they are able to use English and Bahasa as means of oral and written communication. REFERENCES Ary, D., Jacobs, L. C., & Sorensen, C. K. (2010). Introduction to Research inEducation (8 ed.). Wadsworth: Cengage Learning. Beeby, C. E. (1979). Indonesian Education, an Experiment in Assessment. Willington: Oxford University Press. Brown, G., & Yule, G. (1983). Teaching the Spoken Language. New York: Cambridge University Press. Brown, H. D. (2000). Principles of Language Learning and Teaching (4 ed.). White Plains: Longman. Ellis, R. (1997). Second Language Acquisition. Oxford: Oxford University Press. Ellis, R. (2008). The Study of Second Language Acquisition (2 ed.). New York: Oxford University Press. Ellis, R., & Barkhuizen, G. (2005). Analysing Learner Language. Chennai: Oxford University Press. Harashima, H. D. (2006). An Error Analysis of the Speech of an Experienced Japanase Learner of English. (6), 37-58. Harmer, J. (2007a). How to Teach English. Harlow: Pearson. Harmer, J. (2007b). The Practice of English Language Teaching (4 ed.). Harlow: Pearson. Hendrickson, J. (1983). Error Analysis and Error Correction in Language Teaching. Tanglin: Seamo Regional Language Center. Hughes, R. (2002). Teaching and Researching Speaking. Harlow: Pearson Education. James, C. (1998). Errors in Language Learning and Use Exploring Error Analysis. Harlow: Longman. Kemendiknas. (2006). Standar Isi Untuk Satuan Pendidikan Dasar dan Menengah. Jakarta: Badan Standar Nasional Pendidikan. Luoma, S. (2004). Assessing Speaking. Cambridge: Cambridge University Press. McKay, P. (2006). Assessing Young Language Learners. Cambridge: Cambridge University Press. Prastiwi, A. (2013). A Study of Content and Organization Produced by the Eight Grade Students of SMP Negeri 1 Kudu Jombang in Writing Recount Text. Bachelor Degree, State University of Surabaya, Surabaya. Ramli, D. (2013). An Analysis on Students' Errors in Writing Recount Text. Research Journal. Richard, J. C. (1974). Error Analysis: perspective on second langauge acquisition. London: Longman. Santrock, W.J. (2008). Psikologi Pendidikan (2 ed.). Jakarta: Kencana. Schrampfer, A. B. (1991). Undertsanding and Using English Grammar (3 ed.). New York: Pearson Education. Secretariat, L. (2012). Engaging in and Exploring Recount Writing. Adelaide: Government of South Australia. Sobur, Alex. (2011). Psikologi Umum Dalam Lintasan Sejarah. Bandung: Pustaka Setia. Tarone, E., Swierzbin, B. (2009). Exploring Learner Language Oxford: Oxford University Press. Wenden, A., & Rubin, J. (1987). Learner Strategies in Language Learning. Hemel Hempstead: Prentice Hall International. Zakiah, N. (2012). Grammatical Error Analysis in Recount Text Made by the Eight Graders of SMP Negeri 1 Mojosari. Bachelor Degree, State University of Surabaya, Surabaya.